Penegakan Hukum Terhadap Judi Online Pada Masa Pandemi Covid-19 - Singadji, Widya Natalia; Hehanussa, Deassy Jacomina Anthoneta; Supusepa, Reimon (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The crime rate in Indonesia has increased during the Covid-19 pandemic, this is because many people have been laid off (Termination of Employment) so that many do things that are against the law because they are faced with economic problems, one of which is by playing online gambling (togel) which is used as entertainment in the midst of this pandemic or as a livelihood for some people.Purposes of the Research: The purpose of this study is to analyze and explain the mechanism of law enforcement against online gambling during the Covid-19 Pandemic, as well as analyze and explain the obstacles encountered by law enforcement officers in dealing with online gambling during the Covid-19 Pandemic.Methods of the Research: The method used is normative juridical with a statutory approach, a conceptual approach and a case approach. Sources of legal materials used are primary and secondary. The technique of collecting is through literature study and analyzed by means of description using qualitative methods.Results of the Research: The process of law enforcement during the Covid-19 pandemic is the same as before the pandemic, but the process must implement health protocols and the implementation of Rapid Tests for perpetrators and witnesses, in the process of examining witnesses before the Covid-19 pandemic can be examined at once but during the Covid-19 pandemic the examination Witness must have a regulated distance or the examination mechanism cannot be done all at once, this is what slows down the examination process.